Effect of micronutrient supplements on low-risk pregnancies in high-income countries: a systematic quantitative literature review. Issue 13 (9th September 2020) - James-McAlpine, Janelle M; Vincze, Lisa; Vanderlelie, Jessica J; Perkins, Anthony V
Abstract: Objective: To assess the quantity and focus of recent empirical research regarding the effect of micronutrient supplementation on live birth outcomes in low-risk pregnancies from high-income countries. Design: A systematic quantitative literature review. Setting: Low-risk pregnancies in World Bank-classified high-income countries, 2019. Results: Using carefully selected search criteria, a total of 2475 publications were identified, of which seventeen papers met the inclusion criteria for this review. Data contributing to nine of the studies were sourced from four cohorts; research originated from ten countries. These cohorts exhibited a large number of participants, stable data and a low probability of bias. The most recent empirical data offered by these studies was 2011; the most historical was 1980. In total, fifty-five categorical outcome/supplement combinations were examined; 67·3 % reported no evidence of micronutrient supplementation influencing selected outcomes. Conclusions: A coordinated, cohesive and uniform empirical approach to future studies is required to determine what constitutes appropriate, effective and safe micronutrient supplementation in contemporary cohorts from high-income countries, and how this might influence pregnancy outcomes.